A Systematic Review of Digital Picture Storybooks as Multimodal Tool for Literacy Development in Students with Mild Intellectual Disabilities - Anjelina, Dewi; Handayani, Langlang; Widyatmoko, Arif; Subali, Bambang (FKIP - Universitas Riau, 2026)
The rapid advancement of digital technology has encouraged the integration of digital picture storybooks as instructional media that combine text, images, audio, and animation to support multimodal learning. Although their use in literacy instruction has increased, empirical evidence regarding the effectiveness of digital picture storybooks for students with mild intellectual disabilities remains fragmented and has not been systematically synthesized. This study aims to systematically review empirical research published between 2020 and 2025 on the use of digital picture storybooks as multimodal instructional tools for literacy development in students with mild intellectual disabilities. A systematic literature review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Relevant studies were identified through searches of national and international academic databases using predefined inclusion and exclusion criteria. The selected studies were screened and analyzed using descriptive and thematic synthesis. The findings indicate that digital picture storybooks have the potential to support literacy development, particularly in vocabulary acquisition, basic reading comprehension, and learner engagement among students with mild intellectual disabilities. Overall, this review suggests that digital picture storybooks can function as effective multimodal literacy tools when implemented with appropriate instructional support, while highlighting the need for further studies.